Association between use of non–vitamin k oral anticoagulants with and without concurrent medications and risk of major bleeding in nonvalvular atrial fibrillation - Chang, Shang-Hung; Chou, I-Jun; Yeh, Yung-Hsin; Chiou, Meng-Jiun; Wen, Ming-Shien; Kuo, Chi-Tai; See, Lai-Chu; Kuo, Chang-Fu (American Medical Association, 2017)
Importance:  Non–vitamin K oral anticoagulants (NOACs) are commonly prescribed with other medications that share metabolic pathways that may increase major bleeding risk.